GAMBARAN PENGETAHUAN BANTUAN HIDUP DASAR (BHD) PADA ANGGOTA KELUARGA YANG MEMILIKI FAKTOR RISIKO PENYAKIT JANTUNG DI DENPASAR TIMUR - Ni Luh Made Citraning Hadi Pertiwi; I Kadek Saputra; I Gusti Ngurah Juniartha (Coping: Community of Publishing in Nursing, 2021)
Cardiac arrest has a higher risk in general population with risk factor for heart disease. About 70% of cardiac arrests occur at home and families have a vital role in giving first aid with Basic Life Support (BLS). Adequate knowledge, willingness, and skills are needed to be able to perform BLS properly. There is not much study related to the knowledge of family members with history of heart disease in Denpasar. The purpose of this study was to determine the description of BLS knowledge in family members with heart disease risk factors. This study is an observational descriptive study conducted in the area of Public Health Center I Denpasar Timur with 96 research respondent recruited using a purposive sampling technique. The majority of respondent: 62.5% were female, 32.29% in their late teens, 51.04% had a tertiary education level, 82.3% had never attended BLS training, and 51% had been exposed to BLS information. According to the findings of this study, the majority of the respondent' knowledge is classified as sufficient (70.8%). In general, the study respondent had a good understanding (96.9%) of the definition of BLS and a sufficient understanding of the principles of BLS (53.1%). The study concluded that the majority of the respondent' knowledge is adequate. The public health center is expected to be able to maintain and increase public knowledge of family members with heart disease risk factors in order to increase knowledge and teach BLS skills, one of which is through BLS training.